KEDUDUKAN LAPORAN KETERANGAN PERTANGGUNGJAWABAN KEPALA DAERAH KEPADA DEWAN PERWAKILAN RAKYAT DAERAH BERDASARKAN UNDANG-UNDANG NO. 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH - WAHYU ADHA RAHMANSYAH; Ikhsan '; Dodi Haryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Results reveal that the position of Regional Head Report on the regional administration is a duty officer who delivered Parliament in each year and end tenure with a particular mechanism. While the function Report on the Regional Head as a benchmark to determine the success or failure of the Regional Head in carrying out its duties during a certain period, and increased efficiency, effectiveness, productivity and accountability by monitoring the implementation of the Local Government Council. Nevertheless, the obligation Report on the Regional Head does not have legal consequences against the dismissal of the Head of Region as contained in Law No. 32 Year 2004 on Regional Government. Constraints associated judicial accountability report. Regional Head of the Parliament by Law Number 32 Year 2004 regarding Regional Head ie the absence of strict sanctions against the delay in the implementation of the accountability report, there is no clear legal consequences of the poor performance achievement in the Regional Head accountability report, and the lack of accountability and transparency mechanisms for the accountability report society.Keyword : Position, Funtion and Acoubntability of regional heads.